Aplikasi Pengukuran Luas Daun Tanaman Menggunakan Pengolahan Citra Digital Berbasis Android - Andrian, Rico; Agustiansyah, Agustiansyah; Junaidi, Akmal; Lestari, Dian Indah (JURNAL AGROTROPIKA, 2022)
Leaves are the most important organ in plants in the process of photosynthesis and will affect plant growth and productivity. Leaves also have a function as the main food maker. Leaf area is a very important parameter in the science of plant nutrition, measurement of plant protection, the relationship between water and soil in plants, plant ecosystems, plant fertility, etc. The use of leaf area measuring instruments that exist today has its drawbacks in terms of portability and practicality. The development of smartphone technology, one solution that can be used to overcome this is to design an application to measure the area of leaves by utilizing an android based smartphone camera. This research has been successfully made a leaf area calculation application that utilizes smartphone cameras using the OpenCV library. The application provided in this study is able to provide convenience and speed up the calculation of the leaf image area with an error rate of 4.9% and an accuracy of 95.1% from the average results of 10 leaf samples tested. Keywords : Image Processing, Leaf Area, Opencv, Android.